Prevalence and risk factors of neurodevelopmental disorders among migrant and refugee preschool children in high-income western countries: A systematic review and meta-analysis protocol - Kh Shafiur Rahaman; Valsamma Eapen; Mythily Subramanium; James Rufus John; Kanchana Ekanayake; Amit Arora (PLoS ONE, 2025)
Neurodevelopment is a complicated mechanism involving genetic, cognitive, emotional, and behavioural processes. Factors related to parental migration directly or indirectly affect their children’s neurodevelopmental process and may lead to neurodevelopmental disorders (NDDs). Other factors, such as barriers to accessing health services, social discrimination, mothers’ psychosocial health during pregnancy may disrupt the neurodevelopmental process and lead to disorders and disabilities among children of migrants. However, there is a gap in data on the prevalence and the risk factors of neurodevelopmental disorders among migrant children, which have been inadequately listed. This paper presents a protocol for a systematic review to study and synthesise published evidence to ascertain the global prevalence of neurodevelopmental disorders and risk factors leading to those groups of neurodevelopmental disorders among children of migrants in high-income Western countries. The protocol for this systematic review was developed with guidance from the Joanna Briggs Institute (JBI) methodology and reported as per the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) statement. Observational studies that report on the prevalence and risk factors of neurodevelopmental disorders among migrant young children under 5 years of age in high-income Western countries will be included in this study. Five electronic databases will be searched comprehensively (MEDLINE, EMBASE, CINAHL, PsycINFO, and Scopus). Two reviewers will independently screen, select studies, assess the methodological quality, and extract all relevant data subsequently. The systematic review and meta-analysis will help design tailored interventions for migrant and refugee preschool children with neurodevelopmental disorders and identify gaps from previous research to guide future research. This review is registered with PROSPERO (CRD42024589357).